Identification and genomic characterization of bovine parvovirus 1 in yaks. (November 2021) - Shao, Guoqing; Zhao, Long; Tang, Cheng; Yue, Hua
Bovine parvovirus 1 (BPV1) is a causative agent of respiratory, gastrointestinal, and reproductive cattle diseases. We collected 149 yak diarrhea fecal samples from 9 farms in the Qinghai-Tibet Plateau. The samples were screened for BPV1 by PCR, and 2 samples were positive for BPV1. The complete genomes of these BPV1 isolates were sequenced successfully. The sequences of these 2 variants were both 5, 515 bp in length and shared 96.5–96.8% identity with 2 previously reported BPV1 genomes (GenBank DQ335247, NC_001540). Twenty-six identical amino acid mutations were found in the 2 yak variants, including 7 amino acid substitutions in receptor-binding regions of the VP2 protein, and 5 amino acid substitutions in the NS1 protein C-terminal region that functions to activate transcription. The new genome sequences contribute to better understanding of the evolution and molecular characteristics of BPV1.